2013
DOI: 10.1186/1479-5868-10-17
|View full text |Cite
|
Sign up to set email alerts
|

Intervention effects on physical activity: the HEIA study - a cluster randomized controlled trial

Abstract: BackgroundAlthough school-based interventions to promote physical activity in adolescents have been suggested in several recent reviews, questions have been raised regarding the effects of the strategies and the methodology applied and for whom the interventions are effective. The aim of the present study was to investigate effects of a school-based intervention program: the HEalth in Adolescents (HEIA) study, on change in physical activity, and furthermore, to explore whether potential effects varied by gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
137
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(141 citation statements)
references
References 37 publications
3
137
1
Order By: Relevance
“…Sufficiently intense intervention (daily expert-led physical education) and adequate duration (1 year) were two strengths that were pointed out in the successful KISS study, which managed to favourably affect estimates of body composition in first and fifth grade schoolchildren 24. Additionally, both the control group and the intervention group in the present study increased their total physical activity significantly during the intervention 15. This was unexpected as a decline in physical activity with increasing age has repeatedly been documented between the ages 9 and 15 25–27.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Sufficiently intense intervention (daily expert-led physical education) and adequate duration (1 year) were two strengths that were pointed out in the successful KISS study, which managed to favourably affect estimates of body composition in first and fifth grade schoolchildren 24. Additionally, both the control group and the intervention group in the present study increased their total physical activity significantly during the intervention 15. This was unexpected as a decline in physical activity with increasing age has repeatedly been documented between the ages 9 and 15 25–27.…”
Section: Discussionmentioning
confidence: 66%
“…Unintentionally, the intervention components may therefore have been better adapted and delivered to girls than to boys. The earlier demonstrated intervention effects on behaviours in girls but not in boys may partly explain why the intervention was effective on BMI and BMIz among girls only 14 15. It is possible that boys did not change their physical activity level as much as girls because of higher baseline values and, consequently, had a smaller potential for change.…”
Section: Discussionmentioning
confidence: 98%
“…From a total of 27 initial potentially eligible papers , a final number of 10 eligible and included papers was obtained for study aim 1 (to identify changes in SB longitudinally) and 3 eligible papers for study aim 2 (associations between changes in SB and changes in adiposity), and the process is described in Fig. a,b.…”
Section: Resultsmentioning
confidence: 99%
“…Study methodological quality (Table ) for study aim 1 was high: all the 10 eligible papers were rated as ≧70% . For studies reporting change in SB, agreement during the methodological quality assessment was 95% ( k = 0.77) on the 80 items.…”
Section: Resultsmentioning
confidence: 99%
“…The seven-day measurement time period was used for the present study as it provides reliable (R > 0.76) estimation of children' physical activity levels [33] but this was difficult to implement as only 63% of children had close to 6 days at baseline and 45% had close to 5 days of valid wear time at follow up. A large-scale study found that there was 15% reduction from baseline to follow-up in the number of participants having 5 valid days of accelerometer wear time following a 20-month intervention [34]. Children may not want wear accelerometers due to negative peer pressure, forgetfulness, or discomfort [35].…”
Section: Discussionmentioning
confidence: 99%